Acontecimentos do cinema brasileiro contemporâneo: Amarelo Manga, Carandiru, Última Parada 174 - Recart, Juliana Santos (Universidade do Vale do Rio dos Sinos, 2011)
It is assumed in this research the principal that all objects situated within the audiovisual are manufactured; they are imaginary creations in which are formed from an aggregation of technical procedures. These objects are called, in this research, of audiovisual ethicities. Considering its vast territory, the national cinema presents a variety of identities, which are merged to form the Brazilian Cinema. While analyzing the national cinema, I hoped to demonstrate how certain senses were framed from practices executed by the directors. The research's empirical object is constituted of three contemporary pieces: Amarelo Manga (Cláudio Assis/2003), Carandiru (Hector Babenco/2003), and Última Parada 174 (Bruno Barreto/2008). These films, independently of classifications, introduce senses to the world, are able to communicate indivisible thoughts about the ambience in which they were produced, and nourish the imaginary through its conceptual reality. I recognize such senses as the cinematographic events.
Keywords: Acontecimento; Sentido; Cinema brasileiro; Cinematographic event; Sense; Brazilian cinema; ACCNPQ::Ciências Sociais Aplicadas::Comunicação